2019
DOI: 10.1002/pds.4736
|View full text |Cite
|
Sign up to set email alerts
|

Causal inference for evaluating prescription opioid abuse using trend‐in‐trend design

Abstract: Purpose One response to the opioid crisis in the United States has been the development of opioid analgesics with properties intended to reduce non‐oral use. Previous evaluations of abuse in the community have relied on population averaged interrupted time series Poisson models with utilization offsets. However, competing interventions and secular trends complicate interpretation of time‐series analyses. An alternative research design, trend‐in‐trend, accounts for heterogeneity in per capita opioid dispensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…In our earlier study of national dispensing patterns, we noticed that new opioid analgesics were initially prescribed in locations that hosted phase III clinical trials for that product, tertiary care and teaching hospitals, and well-established advanced pain management clinics with multi-state catchment areas [ 30 ]. The hypothesis is also consistent with our previous analysis, where we found that early high-dispensing locations for new branded opioids was geographically concentrated and sometimes corresponded to phase 3 clinical trial sites [ 31 ], a phenomenon reported in a much earlier study [ 32 ] but given little attention until recently [ 33 ].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our earlier study of national dispensing patterns, we noticed that new opioid analgesics were initially prescribed in locations that hosted phase III clinical trials for that product, tertiary care and teaching hospitals, and well-established advanced pain management clinics with multi-state catchment areas [ 30 ]. The hypothesis is also consistent with our previous analysis, where we found that early high-dispensing locations for new branded opioids was geographically concentrated and sometimes corresponded to phase 3 clinical trial sites [ 31 ], a phenomenon reported in a much earlier study [ 32 ] but given little attention until recently [ 33 ].…”
Section: Introductionsupporting
confidence: 91%
“…A common narrative has been that nonmedical opioid use increased in the United States because outpatient extended-release opioids became more widely used by those without formal pain management credentials or specialization [54][55][56][57]. From the findings of this survey and our previous work [31], we propose a complementary hypothesis that early adopters may have different approaches to opioid risk management. If confirmed by further investigation, this observation may impact the interpretation of FDA-mandated assessments of Risk Evaluation and Mitigation Strategies (REMS) that occur 18 months and 3 years after launch [58].…”
Section: Discussionmentioning
confidence: 83%
“…Current design trends and future development of craft require sustainable development strategies, explaining export opportunities and the situation when product creation is new, especially knowledge about trend craft design. Trends focus on standout products with an independent timeline in the global market (Dasgupta et al, 2019). Exploration of existing forms is the development of new products based on existing products.…”
Section: Resultsmentioning
confidence: 99%